Systemic Functional Linguistics (SFL) and Translation - Muhammad Fauzan Aminudin (LINGUA : Jurnal Bahasa, Sastra, dan Pengajarannya, 2023)
Language as a fundamental part to communicate with other people becomes crucial since it engages other disciplines. Many of the communication products are in English which might bring difficulties to understand or interpret the meaning due to the language variations. SFL can bridge the meaning and context which usually becoming a problem faced by the translators. This article aims to depict a brief concept of SFL and translation and attempts to figure out the relationship among linguistics and translation, especially the implementation of SFL in translation field. The article elaborates ideas from several experts in linguistics, specifically in SFL and translation. This revealed that SFL promoted by linguist named M.A.K Halliday linked and can be applied in translation. It is crystal clear that SFL also has a role in developing the theory of translation that can be proved by Juliana House in the book A Model for Translation Quality Assessment (1977) and Roger Bell in book entitled Translation and Translating: Theory and Practice (1991).